Nexus Capacity Scorecard (NCS): guidance note and tool - Khalid, Sidra; Elias, M. (International Water Management Institute, 2024)
The Water–Energy–Food–Ecosystem (WEFE) nexus approach represents a holistic and interconnected perspective for addressing the complex interdependencies among water, energy, food, and ecosystems. This integrated perspective highlights the importance of managing WEFE resources collaboratively to achieve social, economic, and environmental sustainability. The Nexus Capacity Scorecard (NCS) is part of a toolkit developed to gauge capacities to adopt a WEFE nexus approach within and/or across institutions working in the water, energy, food/agriculture, and environmental sectors (henceforth referred to as ‘WEFE institutions’). The NCS supports the self-assessment of institutional processes, readiness, and capacities in relation to WEFE approaches. The purpose is to identify opportunities, possible gaps, and inform the planning of tailored WEFE nexus capacity-building efforts, programs and interventions, and/or their monitoring over time. The scorecard can also be used as a launchpad for discussions, within and across organizations and sectors, for improving WEFE nexus practice and collaboration.